Macromol. Theory Simul. 2/2017. Issue 2 (March 2017) - Oya, Yutaka; Kikugawa, Gota; Okabe, Tomonaga
Abstract : Front Cover : Amorphous structure of DGEBA/33DDS epoxy resin obtained by the chemical curing simulation implemented in a molecular dynamics (MD) method. The maximum crosslinked molecule is highlighted by green. An appropriate amorphous material is selected using data‐driven clustering approach that combines a MD simulation and self‐organizing maps. This is reported by Yutaka Oya, Gota Kikugawa, and Tomonaga Okabe* in article number 1600072.